PERBEDAAN KADAR INTERLEUKIN-6 PADA PENDERITA DIABETES MELITUS TIPE 2 TERKONTROL DAN TIDAK - Angga Eka Kurniawan; Aulia Risqi Fatmariza (Jurnal Kesehatan, 2024)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic, non-communicable disease that progresses slowly due to multifactorial etiology. Chronic low-grade inflammation plays an important role in the pathogenesis of T2DM, thereby linking diabetes to a number of common conditions thought to originate from inflammatory mechanisms. IL-6 is considered an independent risk factor and acts as a marker of insulin resistance and development of T2DM. High extracellular glucose levels will trigger an increase in oxidative stress which will increase ROS production and lead to inflammation. Objective: To prove that there are differences in IL-6 levels in controlled and uncontrolled T2DM sufferers. Research method: The type of research is analytical observational, with a cross sectional research design and non-probability sampling technique with a purposive sampling method in the laboratory of RSU Muhammadiyah Roemani Semarang in November-December 2022. Results: The results of the study showed that the mean value of IL-6 levels in T2DM controlled at 4.37 pg/ml and uncontrolled T2DM at 76.07 pg/ml. Based on Mann-Whitney U statistical analysis, it was found that the p value was <0.05, thus proving that there was a significant difference in IL-6 levels in controlled and non-controlled T2DM sufferers. Conclusion: There is a difference in IL-6 levels in controlled and uncontrolled T2DM sufferers, where IL-6 levels in uncontrolled T2DM sufferers are higher than in controlled T2DM sufferers.